Tobacco Smoking Increases Methylation of Polypyrimidine Tract Binding Protein 1 Promoter in Intracranial Aneurysms - Wang, Zhepei; Zhou, Shengjun; Zhao, Jikuang; Nie, Sheng; Sun, Jie; Gao, Xiang; Lenahan, Cameron; Lin, Zhiqin; Huang, Yi; Chen, Gao (Frontiers in Aging Neuroscience, 2021)
DNA methylation at the gene promoter region is reportedly involved in the development of intracranial aneurysm (IA). This study aims to investigate the methylation levels of polypyrimidine tract-binding protein 1 (PTBP1) in IA, as well as its potential to predict IA. Forty-eight patients with IA and 48 age- and sex-matched healthy controls were recruited into this study. Methylation levels of CpG sites were determined via bisulfite pyrosequencing. The PTBP1 levels in the blood were determined using a real-time quantitative reverse transcription-polymerase chain reaction test. Significant differences were found between IAs and controls in CpG1 (p = 0.001), CpG2 (p < 0.001), CpG3 (p = 0.037), CpG4 (p = 0.003), CpG5 (p = 0.006), CpG6 (p = 0.02), and mean methylation (p < 0.001). The mRNA level of PTBP1 in the blood was much lower in IAs compared with controls (p = 0.002), and the PTBP1 expression was significantly associated with DNA methylation promoter levels in individuals (r = −0.73, p < 0.0001). In addition, stratification analysis comparing smokers and non-smokers revealed that tobacco smokers had significantly higher levels of DNA methylation in PTBP1 than non-smokers (p = 0.002). However, no statistical difference in PTBP1 methylation was found between ruptured and unruptured IA groups (p > 0.05). The ROC analyses of curves revealed that PTBP1 methylation may be a predictor of IA regardless of sex (both sexes, area under curve (AUC) = 0.78, p < 0.0001; male, AUC = 0.76, p = 0.002; female, AUC = 0.79, p < 0.0001). These findings suggest that long-term tobacco smoke exposure led to DNA methylation in the promoter region of the PTBP1 gene, which further decreased PTBP1 gene expression and participated in the pathogenesis of IA. The methylation of PTBP1 may be a potential predictive marker for the occurrence of IA.